Outcome of Patients With Metastatic Chromophobe Renal Cell Carcinoma Treated With Sunitinib. (5th July 2016) - Keizman, Daniel; Sarid, David; Lee, Jae L.; Sella, Avishay; Gottfried, Maya; Hammers, Hans; Eisenberger, Mario A.; Carducci, Michael A.; Sinibaldi, Victoria; Neiman, Victoria; Rosenbaum, Eli; Peer, Avivit; et al.
Abstract : Background: Sunitinib is a standard treatment for metastatic clear cell renal cell carcinoma (mccRCC). Data on its activity in the rare variant of metastatic chromophobe renal cell carcinoma (mchRCC), are limited. We aimed to analyze the activity of sunitinib in a relatively large and homogenous international cohort of mchRCC patients in terms of outcome and comparison with mccRCC. Methods: Records from mchRCC patients treated with first-line sunitinib in 10 centers across 4 countries were retrospectively reviewed. Univariate and multivariate analyses of association between clinicopathologic factors and outcome were performed. Subsequently, mchRCC patients were individually matched to mccRCC patients. We compared the clinical benefit rate, progression-free survival (PFS), and overall survival (OS) between the groups. Results: Between 2004 and 2014, 36 patients (median age, 64 years; 47% male) with mchRCC were treated with first-line sunitinib. Seventy-eight percent achieved a clinical benefit (partial response + stable disease). Median PFS and OS were 10 and 26 months, respectively. Factors associated with PFS were the Heng risk (hazard ratio [HR], 3.3; p = .03) and pretreatment neutrophil-to-lymphocyte ratio (NLR) >3 (HR, 0.63; p = .02). Factors associated with OS were the Heng risk (HR, 4.1; p = .04), liver metastases (HR, 3.8; p = .03), and pretreatment NLR <3 (HR, 0.55; p = .03). Treatment outcome was not significantly different between mchRCC patients and individually matched mccRCC patients. In mccRCC patients ( p value versus mchRCC), 72% achieved a clinical benefit ( p = .4) and median PFS and OS were 9 ( p = .6) and 25 ( p = .7) months, respectively. Conclusion: In metastatic chromophobe renal cell carcinoma, sunitinib therapy may be associated with similar outcome and toxicities as in metastatic clear cell renal cell carcinoma. The Heng risk and pretreatment NLR may be associated with PFS and OS. Abstract : This study analyzed the activity of sunitinib in a relatively large and homogenous international cohort of metastatic chromophobe renal cell carcinoma in terms of outcome and comparison with a matched cohort of metastatic clear cell renal cell carcinomas. Sunitinib therapy may be associated with outcome and toxicities similar to those seen with metastatic clear cell renal cell carcinoma. The Heng risk and pretreatment neutrophil-to-lymphocyte ratio may be associated with progression-free survival and overall survival.